Plan de negocio: DALA Cervecería Artesanal (2020)
It is a business plan for a craft brewery, developed under cogotá city context. In which the situation of the global and Colombian market was analyzed, the company was structured, sales and market strategies were planned, direct and indirect competition was analyzed, and economic viability was analyzed.